Analysis of inter-expert agreement when working with the AOSpine classification (TLCS, 2013): our experience, questions and contradictions - Andrey V. Dydykin; Konstantin S. Yashin; Andrey E. Bokov; Sergey G. Mlyavykh (Хирургия позвоночника, 2019)
Objective. To assess inter-expert agreement among spine surgeons having different levels of clinical experience when working with the AOSpine classification (TLCS, 2013). Materials and Methods. The study involved nine surgeons divided into three equal groups depending on work experience. All respondents were asked to classify the MSCT data of 50 patients with acute injuries to the thoracic and lumbar spine pursuant to TLCS (2013) classification. To evaluate inter-expert agreement, a Kappa coefficient interpreted according to Landis – Koch criteria was used. Results. The overall coefficient of inter-expert agreement for all observations among all groups of respondents was 0.43, which reflects a moderate level of agreement. Moderate inter-expert agreement was revealed for injury types A (0.45) and C (0.56), and satisfactory – for type B (0.34). The highest levels of agreement were obtained for subtypes A1 (0.67) and A4 (0.80) in the group of advanced specialists and for type C (0.70) in the group of specialists with a basic level of experience. Conclusion. The study demonstrated predominantly moderate level of inter-expert agreement when working with the AOSpine classification (TLCS, 2013). The accuracy of its use increases with a gain in practical experience of a surgeon.